Forgotten and unattended: refugees in post-earthquake Japan - Katsunori Koike (Forced Migration Review, 2011)
Despite being a world leader in disaster preparedness, Japan paid scant attention to the needs of one of its most marginalised social groups after the 2011 earthquake.